Development of Muslim Economic Thinking in India in 20th Century - Bilal Ahmad Ganaie (Penerbit Hellow Pustaka, 2026)
The evolution of Muslim economic thought in India throughout the 20th century signifies a notable intellectual response to the socio-economic and political changes instigated by colonial rule, the decline of traditional Islamic institutions, and the rise of modern capitalist and socialist ideologies. This study aims to explore the development of Islamic economic discourse among Indian Muslim scholars, reformers, and institutions during this period. Central to this discourse were the efforts to reconstruct a comprehensive economic system grounded in Islamic principles, including the prohibition of riba (usury), gharar (excessive uncertainty), maisir (gambling), and the principles of profit and loss sharing. This paper seeks to examine the foundational framework of Muslim economic thought in India during the 20th century. Key figures such as Manazir Ahsan Gilani, Muhammad Hamidullah, Hafizur Rehman Seohwari, Anwar Iqbal Qureshi, Shaikh Mahmud Ahmad, Abul Ala Mawdudi, M. N. Siddiqi, Muhammad Uzair, Ausaf Ahmad, F. R. Faridi, Abdul Hasib, M. H. Khatkhatay, Azim Ihsan Islahi, and M. Obaiduallah significantly contributed to presenting a systematic critique of Western economic models while proposing a comprehensive Islamic alternative. Furthermore, this study analyzes the role of Islamic economists, bankers, and key figures in shaping this discourse, which ultimately led to the establishment of various interest-free cooperative credit societies, Islamic financial societies, financial associations, and Islamic financial investment companies located in both northern and southern India. The objective of this paper is to understand the indigenous roots of these developments